MicroRNA let-7 Suppresses Influenza A Virus Infection by Targeting RPS16 and Enhancing Type I Interferon Response - Wu, Wenjiao; Wang, Chao; Xia, Changliang; Liu, Shuwen; Mei, Qinghua (Frontiers in Cellular and Infection Microbiology, 2022)
Given the frequent emergence of drug-resistant influenza virus strains and new highly pathogenic influenza virus strains, there is an urgent need to identify new antiviral drugs and targets. We found that influenza A virus (IAV) infection caused a significant decrease of microRNA let-7 expression in host cells; that overexpression of let-7 increased interferon expression and effectively inhibit IAV infection; and that let-7 targets the 3’-untranslated region (UTR) of the ribosomal protein 16 (RPS16) gene, decreasing its expression. Knocking down the expression of RPS16 increased the expression of type I interferon and inhibited viral replication. The present study uncovered the regulatory effect of let-7b and let-7f on influenza A infection, which is a potential biomarker of IAV infection. In addition, let-7 may be a promising therapeutic agent against influenza A.